1997
DOI: 10.1073/pnas.94.7.2838
|View full text |Cite
|
Sign up to set email alerts
|

Unwinding of the box I element of a herpes simplex virus type 1 origin by a complex of the viral origin binding protein, single-strand DNA binding protein, and single-stranded DNA

Abstract: The herpes simplex virus type 1 (HSV-1) genome contains three origins of replication: ori L and two copies of ori S . These origins contain specific sequences, box I and box II, linked by an AT-rich segment, that are recognized by an HSV-1-encoded origin binding protein (UL9 protein) which also possesses DNA helicase activity. Despite its intrinsic helicase activity, the UL9 protein is unable to unwind ori S or the box I element of ori S , either in the presence or absence of the HSV-1-encoded single-strand DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Evidence has been provided that the seven essential proteins, the origin binding protein (OBP), the polymerase with its processivity factor (UL30 and UL42), the trimeric primase-helicase complex (UL52, UL5, and UL8), and ICP8, accumulate in punctuate prereplicative sites for the assembly of the multiprotein complex, or primosome, which promotes efficient genomic replication (40,71,76). During initiation, ICP8 associates with the carboxy-terminal domain of the OBP at the origin of replication to assist the ATP-dependent bidirectional origin unwinding (3,36,37,45). It enhances the polymerase processivity (29, 50, 61) and stimulates the helicase-primase activity via interaction with the UL8 subunit (4,17,21).…”
mentioning
confidence: 99%
“…Evidence has been provided that the seven essential proteins, the origin binding protein (OBP), the polymerase with its processivity factor (UL30 and UL42), the trimeric primase-helicase complex (UL52, UL5, and UL8), and ICP8, accumulate in punctuate prereplicative sites for the assembly of the multiprotein complex, or primosome, which promotes efficient genomic replication (40,71,76). During initiation, ICP8 associates with the carboxy-terminal domain of the OBP at the origin of replication to assist the ATP-dependent bidirectional origin unwinding (3,36,37,45). It enhances the polymerase processivity (29, 50, 61) and stimulates the helicase-primase activity via interaction with the UL8 subunit (4,17,21).…”
mentioning
confidence: 99%
“…Earlier studies with the box I substrate had led to a model in which destabilization of the AϩT sequence linking boxes I and II to provide a binding site for ICP8 was the first step in the unwinding of Ori S by the UL9 protein (8). Unwinding of Ori S is required to provide an entry site for the replication machinery needed to initiate DNA replication.…”
mentioning
confidence: 99%
“…Previous studies have shown that a complex of the UL9 protein and the HSV-1-encoded single-stranded DNA binding protein, ICP8, can efficiently unwind a duplex box I if it possesses a 3Ј single-stranded tail at least 18 nucleotides in length, positioned downstream of box I (8). These findings suggested a model for the unwinding of Ori S in which a complex of the UL9 protein bound to boxes I and II and ICP8 bound to single-stranded DNA generated at the AϩT-rich linker, possibly as a consequence of transcription (4), unwinds the origin of DNA replication to provide access to the replication machinery, thereby permitting the initiation of DNA replication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional equivalent of Zta in herpes simplex virus 1 (HSV1) is the origin binding protein (OBP) encoded by the HSV1 UL9 gene. The HSV1 OBP is an ATP-dependent DNA helicase that appears to work together with the single-stranded DNA (ssDNA) binding protein ICP8 to accomplish DNA strand separation at the HSV1 origin OriS (25,32). The EBV genome contains an ICP8 orthologue, referred to as BALF2, and a processive helicase (encoded by the BBLF4 gene) but lacks a replication initiator helicase like UL9.…”
mentioning
confidence: 99%